The Effect of Educational Blogs on The Level of Knowledge About Hypertension Among The Productive Age Community in Karawana Village - Glenn Frekly S. Tapa Ngale; Sisilia Rammang; Katrina Feby Lestari (Viva Medika, 2026)
Hypertension, or high blood pressure, is a dangerous noncommunicable disease (NCDs) that generally occurs with age and is often referred to as a silent killer because the symptoms are often invisible or imperceptible in most patients. Therefore, comprehensive education with easy access to information about the disease is necessary. Education through blogs has great potential as an effective tool for raising awareness, especially in controlling hypertension. This study was quantitative in nature. This study used a quasi-experimental design with a one-group pretest-posttest design. The minimum sample size was 30 respondents of productive age, with sampling using purposive sampling based on inclusion and exclusion criteria. Univariate and bivariate data analysis was performed using the Wilcoxon test. Before the intervention, 4 respondents (13.3%) had good knowledge, sufficient knowledge in 12 respondents (40%), and insufficient knowledge in 14 respondents (40.7%). After the intervention, 15 respondents (50%) had good knowledge, 11 respondents (36.7%) had sufficient knowledge, and 4 respondents (13.3%) had insufficient knowledge. The Wilcoxon test showed a p-value of 0.001 (p<0.05), and the effect size (r=0.73) indicated a large effect. There was an effect of the educational blog on the level of knowledge about hypertension among the productive age community in Karawana Village. This study is expected to contribute to the development of education, increase public awareness of hypertension prevention, and encourage the active role of community health centers in providing health education through socialization and blog media.